Optimization of Handling Reports and/or Complaints for the Certainty of Follow-Up to the Settlement of Cases by Demak Police Criminal Investigation Unit - Yuman, Nanda (Advances in Police Science Research Journal, 2024)
Handling of reports and/or complaints is the implementation of the duties and responsibilities of the Demak Police Criminal Investigation Unit in carrying out the investigative function. Good or bad handling of reports and/or complaints has an impact on the certainty of follow-up to the settlement of cases, furthermore on the level of public trust in the Polri institution, especially in the field of law enforcement. The purpose of writing this final project is to describe the organizational resources of the Demak Police Criminal Investigation Unit and the stages of management in handling reports and/or complaints in order to ensure the follow-up of cases. This research is a qualitative type with a field research approach. Data obtained by observation techniques, in-depth interviews, and document study. The theories and concepts used are the theory of management elements, self-competency theory, management function theory, SWOT theory, optimization concepts, reports and/or complaints handling concepts, and the certainty concept of follow-up cases. The results showed that the organizational resources of the Demak Police Criminal Investigation Unit and the management stages in handling reports and/or complaints were not fully adequate and in accordance with relevant police theories, concepts or regulations. In addition, internal and external factors, both supportive and unsupportive, have resulted in the handling of reports and/or complaints by the Demak Police Criminal Investigation Unit to ensure follow-up follow-up of case settlement is not optimal. Therefore, Chief of Demak Police Criminal Investigation Unit as the subject of this final project needs to take steps to solve the problem.